Aerobic and anaerobic capacities in determining adolescent futsal players’ performance levels - Dwi Juniarsyah, Agung; Safei, Imam; Bahri, Samsul; Resmana, Dadan; Fahmi Hasan, Muhamad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Futsal is characterized as a high-intensity sport. Thus, aerobic and anaerobic capacities are essential factors for supporting athletes' performance when competing. Data related to adolescent futsal players in Indonesia still lacked. Therefore, this research objective was to determine how much aerobic and anaerobic abilities became the predictors of futsal athletes’ performance levels. The research method was observational research with a quantitative approach. The research subjects consisted of 15 Regional Training Center (PELATDA) athletes and 15 non-PELATDA athletes from West Java with an average of (age= 18.23 ± 1.13 years old, height= 170.23 ± 3.82 cm, body weight 59.57 ± 5.28 kg, BMI 20.56 ± 1.82 kg/m-2, and FAT 10.05 ± 1.29%). The results showed that body mass, body composition, VO2max, peak power, vertical jump, and fatigue index of PELATDA athletes were better than non-PELATDA athletes. Thus, this research could provide an overview for coaches regarding the aerobic and anaerobic capacities standards of adolescent futsal players and could be used as a reference in making an exercise program to improve athletes’ aerobic and anaerobic capacities.